Intravenous Catheter Use for Inferior Lacrimal Canalicular Laceration Reconstruction: A Life Hack in Low Resource Setting: Poster Presentation - Case Series - Ophthalmologist - ISNA KUSUMA NINTYASTUTI; Ni Nyoman Geriputri (Majalah Oftalmologi Indonesia, 2023)
Introduction : Silicone tube was the standard for stenting canaliculi in lacrimal canalicular laceration. But it was not always in stock at a hospital in remote area with low resource. Use of intravenous catheter to exchange the unavailable slicone tube was a possible option. Case Illustration : We reported two cases of inferior canalicular laceration at NTB provincial hospital. Both cases were adult, one female and one male. First case caused by nail and second because of traffic accident. There were no globe involvement in both case. Reconstruction surgeries with monocanalicular approach were performed. Intravenous catheter was used for stenting the canaliculus. First case was using a 24G, the other was 22G. The catheters were well inserted and planned to be removed at3 month. At the day 7 follow-up, the 24G catheter was extruded spontaneously while the patient with 22G was not. Both patients did not complain of profuse tearing. Discussion : The diameter and length of 24G iv catheter were 0.7mm and 19mm, while 22G were 0.9mm and 25mm. The diameters were similar with the silicone tube (0.6mm) and the lengths were long enough to pass the lower and common canaliculus which has a total 15mm long. The catheter in the first case was extruded possibly because in 24G there was only 4mm inside th lacrimal sac. A high pressure air from the nose would push the catheter backward and extruded. The 22G would have 10mm inside the sac. Conclusion : Intravenous catheter was an alternative option for inferior canalicular laceration stenting in low resource setting.